Answer:
The answer to this problem is True.
Answer: (6 , 3)
Step-by-step explanation: Given
x + 3y =15 ------- equation 1
4x + 2y = 30 --------- equation 2
x = 15 - 3y
Put value of x in equation 2
4 (15 - 3y) + 2y = 30
60 - 12y + 2y = 30
-10y = -30
divide by '-10' on both sides
y = 3
now, put value of y in equation 1
x + 3(3) = 15
x + 9 = 15
x = 15 - 9
x = 6
So , (x , y) = (6 , 3)
Answer:
x = 2 ± √11 (I believe)
Step-by-step explanation:
F(a+h)=2(a+h)³=2(a³+3a²h+3h²a+h³)
the second choice is the correct answer.